Benefits and therapeutic applications of the use of Cannabidiol: A literature review of future perspectives (Research, Society and Development, 2023)
Introduction: The use of Cannabis in a medicinal form has been reported since ancient times, as has its use in a narcotic form. As it spread throughout the world, its psychotropic effects gained strength and interest, highlighting components such as delta-9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD). Methodology: the latter is of great scientific interest due to its beneficial effects on diseases such as arthritis, Alzheimer's, Parkinson's, anxiety, schizophrenia and depression. Results and discussion: CBD stands out for its complex therapeutic action, showing promise due to its effectiveness and lower incidence of side effects compared to other medications, but highlights the need for regulation by the National Health Surveillance Agency (Anvisa). Currently, patients who need CBD often turn to the Judiciary due to the State's refusal to provide the medicine. The diversity of CBD's biological targets opens up possibilities for its application for different purposes, encouraging research into new pharmaceutical formulations, pre-clinical trials and clinical trials in humans. Final considerations: The work aims to promote a bibliographical survey on studies and treatments with CBD, exploring its effectiveness and future prospects. However, the association of Cannabis as a recreational drug creates a stigma regarding its medicinal use, it is crucial to understand that, like other medicines, Cannabis, especially CBD, has significant therapeutic potential and should be considered as a valid option in the treatment of various diseases and clinical conditions.